Short Communication: Mosses from Laiwangi-Wanggameti National Park, Sumba, East Nusa Tenggara, Indonesia - Florentina Indah Windadri; Dewi Rosalina (Society for Indonesian Biodiversity, 2020)
Abstract. Windadri F I, Rosalina D. 2020. Short Communication: Mosses from Laiwangi-Wanggameti National Park, Sumba, East Nusa Tenggara, Indonesia. Biodiversitas 21: 538-545. Sumba Island is an island within the Lesser Sunda Islands. Despite the high diversity and the uniqueness of the area, research to explore the biodiversity in the national park have been rarely conducted. This study was aimed to do inventory of mosses diversity in Laiwangi-Wanggameti National Park, Sumba Island, East Nusa Tenggara Province to enrich the limited information regarding biodiversity in the region. The inventory was done using explorative methods at two research sites (i.e. Laiwangi and Wanggameti), mainly around lake, along river banks, stream banks, site of mount tracking trail and forests. All the mosses found in the study site were collected and then identified based on existing literature and herbarium records. We found 33 species of mosses belonging to 24 genera and 16 families. There were 22 species that shared similarity between Sumba Island and the Lesser Sunda Islands. We proposed that there were 11species of mosses as new records of their distribution in the Lesser Sunda Islands. The ecology and taxonomical status of mosses in the study sites were also described in this paper.